2018
DOI: 10.1371/journal.pone.0194591
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of secretome from osteoblasts derived from sclerotic versus non-sclerotic subchondral bone in OA: A pilot study

Abstract: ObjectiveOsteoarthritis (OA) is characterized by cartilage degradation but also by other joint tissues modifications like subchondral bone sclerosis. In this study, we used a proteomic approach to compare secretome of osteoblast isolated from sclerotic (SC) or non sclerotic (NSC) area of OA subchondral bone.DesignSecretome was analyzed using differential quantitative and relative label free analysis on nanoUPLC G2 HDMS system. mRNA of the more differentially secreted proteins were quantified by RT-PCR in cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Whereas a little overlap between differentially regulated genes in both MSCs and chondrocytes was found, SERPINE1 was one molecule showing parallel up-regulation in medial condyle MSCs and chondrocytes. Consistent with our findings SERPINE1 protein was found to be more abundant in the supernatants of cultured osteoblasts derived from sclerotic areas of OA subchondral bone 54 , however in contrast to our study, its mRNA expression was found to be lower in medial condyle chondrocytes, compared to healthy or lateral condyle chondrocytes in another study 55 . These differences can be partially explained by the fact, that SERPINE1 expression is downregulated in chondrocyte culture 56 .…”
Section: Discussionsupporting
confidence: 90%
“…Whereas a little overlap between differentially regulated genes in both MSCs and chondrocytes was found, SERPINE1 was one molecule showing parallel up-regulation in medial condyle MSCs and chondrocytes. Consistent with our findings SERPINE1 protein was found to be more abundant in the supernatants of cultured osteoblasts derived from sclerotic areas of OA subchondral bone 54 , however in contrast to our study, its mRNA expression was found to be lower in medial condyle chondrocytes, compared to healthy or lateral condyle chondrocytes in another study 55 . These differences can be partially explained by the fact, that SERPINE1 expression is downregulated in chondrocyte culture 56 .…”
Section: Discussionsupporting
confidence: 90%
“…56 In addition, slit guidance ligand (SLIT3) and TGF-β1 derived from osteoblasts acts as pro-angiogenic factors to increase the number of type H ECs. [57][58][59] Notably, TGF-β1 derived from osteoclastic resorption is primarily responsible for subchondral angiogenesis in earlystage OA, 60 while the increase in preosteoclast-derived PDGF-BB plays a relatively predominant role in angiogenic and osteogenic differentiation in late-stage OA (figure 2). 61…”
Section: Reviewmentioning
confidence: 99%
“…In addition to osteomyelitis, osteoarthritis is a common joint disease typically characterized by chronic inflammation and altered osteoblast function. It has been demonstrated that osteoblasts produce increased amounts of the inflammatory cytokines IL-6, IL-8, prostaglandin E2 (PGE2), and vascular endothelial growth factor (VEGF); extracellular matrix markers matrix metalloproteinase-9 (MMP-9) and type I collagen; as well as tumor-growth factor beta-1 (TGF-beta 1) in regions of sclerotic bone as compared to normal bone [ 30 , 31 , 57 ]. And, similar to osteomyelitis, regions of osteoarthritis are marked by an imbalance in alkaline phosphatase expression, and a reduction in osteoblast mineralization and bone sialoprotein expression [ 58 , 59 ].…”
Section: Osteoblasts In the Bone Microenvironment As Contributors mentioning
confidence: 99%
“…Under conditions of normal bone homeostasis, there is a tightly regulated balance between bone deposition and resorption, where there is no net bone gain or loss. However, this balance is upset in several pathological conditions, including osteomyelitis, osteoarthritis, and bone metastatic cancers [ 28 , 29 , 30 , 31 ]. In each of these conditions, and especially in osteolytic disease, osteoclasts are overstimulated to degrade bone.…”
Section: Introductionmentioning
confidence: 99%